ANALISIS MUTU PEMBELAJARAN E-LEARNING DI PROGRAM STUDI PENDIDIDKAN AGAMA ISLAM UNIVERSITAS ISLAM MALANG - Ngestin Nur Rohmah; Mohammad Afifullah; Mohammad Eko Nasrullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The existence of the Covid-19 virus outbreak has an effect on the learning procces which requires students to carry out learning activiti at home due to an appeal from the government to prevent the spread of the virus. The problem and purpose of this research is to determite the quality of E-learning during the Covid-19 pandemic at the Islamic Religious Education Study Program, Islamic University of Malang. This research uses a descriptive qualitative approach by using case study research. This research was conducted by interview, observation and documentation, researchers conducted interview through GPM, lecturers and students. The quality of the E-learning process itself can be seen from learning planning, learning implementation, and evaluation. The quality of E-learning out comes is of high quality because it meets a procedures and objectives, satisfactory learning outcomes indicate the quality of learning that has been applied. E-learning is effectively applied during the Covid-19 pandemic. Factors the affect E-learning consist of internal factors, namely the spirit of teaching and learning from lecturers and student themselves, external factors, namely the Covid-19 pandemic and limited internet access or signal interference in certain areas.